Pengembangan Modul Pembelajaran Sanggul Modern - Elisabeth Tri Yekti Handayani (Jurnal Ilmiah Wahana Pendidikan, 2019)
The purpose of this study was to produce a product consisting of a modern bun learning print module and modification at the Diploma III Makeup Study Program, Jakarta State University. Packed in printed form which can be used for independent study. The methodology used is research and development methods. This study uses a Derek Rowntree model consisting of three people, namely planning, preparation, preparation, and preparation and editing. Continuing to test products starting with material experts, linguists and media experts. Furthermore, these products value students, namely 3 people for individual evaluations and 17 people for field evaluations. The results showed the average value of material experts was 3.86, which meant the product was very good, linguists were 3.79, and media experts were 3.83 which meant the product was very good. Then in the trials the average test results of students for the trial trial 3.65 which means the product is very good and in the field trial trials 3.79 agree very well. In conclusion, modern bun learning modules can be discussed well